2019
DOI: 10.1128/jcm.00344-19
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Infection Loads in Mycoplasma genitalium Clinical Specimens by Use of a Commercial Diagnostic Test

Abstract: Mycoplasma genitalium is a common sexually transmitted infection with a propensity to acquire resistance to commonly used antimicrobial therapies. Bacterial load has been linked to patient symptoms and the success of treatment. In this study, we demonstrate methodology to estimate load from routine diagnostic assays using the ResistancePlus MG test (SpeeDx Pty Ltd., Australia). The method gave comparable quantitation to an M. genitalium-specific 16S rRNA quantitative PCR (qPCR; Spearman r = 0.94) for the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In general, the MG parC -AsyHRM assay showed stable performance when there were >20 genomic copies per reaction, and the fluorescent peak decreased slightly according to M. genitalium load. Based on the published results for infection loads of M. genitalium in clinical samples, our method can serve as an ideal tool for clinical antimicrobial stewardship among symptomatic populations ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the MG parC -AsyHRM assay showed stable performance when there were >20 genomic copies per reaction, and the fluorescent peak decreased slightly according to M. genitalium load. Based on the published results for infection loads of M. genitalium in clinical samples, our method can serve as an ideal tool for clinical antimicrobial stewardship among symptomatic populations ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the sensitivity of common mutations (WT, S83N, S83I, S83R, D87Y, and D87N) was as low as 10 copies per reaction in the evaluation with a plasmid. We expect the method to maintain stable and accurate performance when there are ≥20 genomic copies per reaction in the clinical samples, which is significantly less than the infection load of clinical specimens of M. genitalium (5.50 × 10 3 genomes/mL) ( 26 ). Notably, assay 1 can be used independently for routine identification of M. genitalium .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that women with BV show the presence of M. hominis more often and at higher loads than women without BV [ 7 , 32 , 33 ]. Therefore, the detection and quantification of Mollicutes can be used to monitor and treat patients with antibiotics [ 31 , 34 ]. The findings of this study highlight the importance of quantifying M. hominis during routine diagnostic tests, since not only their presence but also their load may influence female sexual health.…”
Section: Discussionmentioning
confidence: 99%
“…15 These findings were consistent with the results of prior studies [19][20][21] ; notably, some studies found that endocervical swabs were more sensitive than urinary specimens, 20,21 presumably because of the lower bacterial load in urine. 22 Endocervical swabs are the routine specimens sent to our laboratory from STI clinics for molecular detection of CT and NG; we perform assays for detection of MG and CT, as recommended by European guidelines. 6 Of note, the relatively low sensitivity of the test with respect to endocervical swabs might also have underestimated the prevalence of MG in our study.…”
Section: Discussionmentioning
confidence: 99%